Fatores críticos de sucesso na implementação do SAP R/3 na Petrobras - Serpa, Patrícia Maria Ramos (2006)
ERP is a very useful IT tool for business, incorporating the best management practices and contributing for speeding up the decision making process, reducing costs, increasing productivity, and adding competitive advantages, as long as the fundamental requirements for success are followed. This research discusses the Critical Success Factors (CSF) in the implementation of Enterprise Resource Planning (ERP) SAP R/3 at Petrobras. Specific objectives of the study were: select research CSF, based on literature review, validating, prioritizing and verifying what’s new or irrelevant in this context; establish positive or negative factors in the implementation of SAP R3 main modules; and verify the effectiveness of implantation of the system at Petrobras. The research was motivated by the complex implantation of an ERP software in a such huge Company with extreme operational diversity. The study was defined as qualitative and exploratory, and it was used the procedure documental research and an unique case study, due to the fact of being a rare and contemporary case. The source for the Critical Success Factors (CSF) was literature review For data collecting, to support the scientific study, a literature and documental review were conducted, a quiz was applied and people were informally interviewed. Data analysis was done based on the quiz answers, having established cause and effect relationships with the other tools used: documents, interviews and theoretical reference. The results of the study confirmed the objectives of the research. The case study CSF were analyzed and prioritized by their relevance. Some deficiencies were observed that can be improved in future implementations. In the validation and prioritization of CSF, new requirements were indicated as more relevant than other classic ones. Differences in performance and effectiveness of SAP R3 modules were observed, but nothing that could’ve been prejudicial to the effectiveness of SAP R/3 implantation at Petrobras.